Complex carbohydrates in foods - Cho, Susan Sungsoo (Marcel Dekker, 2011)
"Explores the effects of complex carbohydrates (starch, gums, and dietary fibers) on human physiological function and establishes an appropriate dietary intake level for inclusion on nutritional labels. Addresses current research, applications, and implementation issues."